What matters in chronic Burkholderia cenocepacia infection in cystic fibrosis: Insights from comparative genomics - Nunvar, Jaroslav; Capek, Vaclav; Fiser, Karel; Fila, Libor; Drevinek, Pavel (PLoS pathogens, 2017)
Burkholderia cenocepacia causes severe pulmonary infections in cystic fibrosis (CF) patients. Since the bacterium is virtually untreatable by antibiotics, chronic infections persist for years and might develop into fatal septic pneumonia (cepacia syndrome, CS). To devise new strategies to combat chronic B. cenocepacia infections, it is essential to obtain comprehensive knowledge about their pathogenesis. We conducted a comparative genomic analysis of 32 Czech isolates of epidemic clone B. cenocepacia ST32 isolated from various stages of chronic infection in 8 CF patients. High numbers of large-scale deletions were found to occur during chronic infection, affecting preferentially genomic islands and nonessential replicons. Recombination between insertion sequences (IS) was inferred as the mechanism behind deletion formation; the most numerous IS group was specific for the ST32 clone and has undergone transposition burst since its divergence. Genes functionally related to transition metal metabolism were identified as hotspots for deletions and IS insertions. This functional category was also represented among genes where nonsynonymous point mutations and indels occurred parallelly among patients. Another category exhibiting parallel mutations was oxidative stress protection; mutations in catalase KatG resulted in impaired detoxification of hydrogen peroxide. Deep sequencing revealed substantial polymorphism in genes of both categories within the sputum B. cenocepacia ST32 populations, indicating extensive adaptive evolution. Neither oxidative stress response nor transition metal metabolism genes were previously reported to undergo parallel evolution during chronic CF infection. Mutations in katG and copper metabolism genes were overrepresented in patients where chronic infection developed into CS. Among professional phagocytes, macrophages use both hydrogen peroxide and copper for their bactericidal activity; our results thus tentatively point to macrophages as suspects in pathogenesis towards the fatal CS.
Keywords: cystická fibróza; Chronic Disease; Cystic Fibrosis; Humans; Burkholderia Infections; infekce bakteriemi rodu Burkholderia; lidé; srovnávací genomová hybridizace; Respiratory Tract Infections; chronická nemoc; Comparative Genomic Hybridization; Burkholderia cenocepacia; infekce dýchací soustavy